JURIDICAL REVIEW OF THE DISTRIBUTION OF INHERITANCE FOR REPLACEMENT HEIRS IN TERMS OF ISLAMIC INHERITANCE LAW AND CIVIL INHERITANCE LAW - Agnes Listya Adeline; Mentor Mella Ismelina Farma Rahayu (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
Islamic inheritance law in its development, in successor heirs aimed at seeking a sense of justice for his heirs. Basically, successor heirs become heirs because their parents who are entitled to inherit die before the heir.The problems are formulated as follows: 1 how is the concept of successor heirs in Islamic law and civil code law, 2 how does substitute heirs compare between Islamic law and civil law. To answer the above problems, the author uses legal research with a normative jurisical approach method, namely legal research carried out by prioritizing examining library materials and documents called secondary and tertiary data. The specification of the study is descriptive analytical, which aims to provide an overview carried out using qualitative means of legal theories and legal doctrines as well as the opinions of Islamic jurists.The results of the research conducted can be concluded that the system of successor heirs in Islamic law and Civil law occurs when the person who connects it to the heir has died before the heir, and must have a legal Nasab relationship with the heir. The comparison of successor heirs in the system of Islamic law and civil law is that they both replace the position of heirs who died before the heir. And there is a difference between Islamic inheritance law and Civil Law in the division received by the heirs he replaces, in Islamic law i.e. heirs in a straight line down, straight line up, and straight line sideways while civil inheritance law the accepted part is the same and successor heirs do not exist for straight line up.